Реформування системи бухгалтерського обліку в державному секторі - Сліпенчук, Г. В. (Ways to Improve Construction Efficiency, 2013)
This paper discusses the main problems to implementing reform of accounting and reporting in the public sector to meet the requirements of international accounting standards.